INFLOW PERFORMANCE RELATIONSHIP PADA RESERVOIR PANAS BUMI - Rochi Habibi, Achmad
Inflow Performance Relationship (IPR) is the relationship representing reservoir conditions based on pressure and production rate, which is used to determine the productivity of a reservoir. IPR is often required to determine the optimum reservoir production rate and is closely related to the type of completion and production facilities that will be used in the development field. During this time, the IPR equation used for geothermal reservoir is Fetkovich’s equation, which is an equation for gas reservoirs and reservoir containing oil and gas phases. Therefore, in this study, the new IPR equations is developed for geothermal reservoir as a function of wellhead pressure and the rate of water vapor on the surface in order to increase the accuracy of calculations in production and field development optimization. Development of this equation is done by using the method of reservoir simulation software and simple arithmetic. The sensitivity of each parameter in the reservoir is also done to determine its effect on the productivity of the reservoir. In the field application, it takes a multirate test method to determine the maximum production capacity reservoir by using the developed equation. Through the developed equations, fluid reservoir production optimization can be performed well.